Estado nutricional y factores asociados de niños y niñas en edad escolar, residentes en zonas mineras del cantón Paquisha - Durán Cuenca, Melina Aydée (2015)
In order to determine the nutritional status of school children of 6 - 12 years old from Paquisha canton, the study of transverse and correlational was performed. In each of the children who were part of the study it was determined: weight, height, serum iron and hematocrit; whose data were entered into the statistical program ANTRHO PLUS WHO, through which the mean, standard deviation (SD) was determined and Z - Score for height / age and BMI / AGE relationship; The study was completed with a socio-economic survey, hygiene habits, knowledge of food to mothers or guardians of children. In Paquisha canton the school children was divided into two groups: high exposure and moderate exposure; while in the Province of Loja, it is taken into account Carigan and Zalapa neighborhood to compare with the two groups of exposure mentioned above. With regards to nutritional status, we can show that in all three zones chronic malnutrition is in a percentage of 20.00% to 26.67%; MEx is the area of greatest chronic malnutrition; regarding obesity in three zones of exposure levels are low; AEx is the zone with highest rate of 4.65%; while overweight highlights to BEx area with 18.89%; mainly affecting the female rural sector. It determined that chronic malnutrition, obesity and overweight have no knowledge related to food, sweets and asepsis practices. Keywords: Nutritional status, Paquisha, Z- Score, mining exhibition areas.